Cultural Visions and Constitutional Reforms in Canada in the 1980s and 90s - T. Espák, Gabriella (Hungarian Journal of English and American Studies, 2021)
On the occasion of the 150th anniversary of the Canadian Confederation, this essay surveys the various visions of society Canada has lived through until recently. Monocultural, bicultural and multicultural models of political identity alternated to clash over the constitution, thereby making it impossible for Aboriginal peoples and the Québécois to deliver nationalist arguments through the wall of liberal egalitarianism. The failure of the Meech Lake Accord (1987) pushed the country towards a federal and identity crisis inasmuch as it failed to reconcile the interests of national minorities with the interest of the nation as a whole within one legal framework. Continuing clashes over the constitution, especially in the Charlottetown Accord (1992), show that inherent cleavages in the body politic have survived, so multiculturalism has only been a partial solution to a population management problem. (GTE)